The European Union as a Distinctive Actor in Global Climate Change Policy - Bağcı, Hüseyin; Kibaroğlu, Ayşegül (Orta Doğu Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, Uluslararası İlişkiler Anabilim Dalı, 2015)
This dissertation focus on the relationship with the international climate change policy and key actors’ positions on global climate negotiations. The main aim of this dissertation is to show that the European Union takes a different position than other international actors in terms of international climate change negotiation and policy. This distinction stems from the founding philosophy of the European Union and its environmentalist tradition. The argument of this dissertation is that whereas nation-states in general, great emitter states in particular, emphasize their national interests regarding climate change issues, the EU behaves in different way. This different behavior stems from the factors of ‘logic of action,’ ‘supranational decision-making mechanism’ and ‘its concern of spreading the EU standards.’ Despite the fact that there are different views on climate change policy among the EU members and the EU (because it is itself a great emitting body), these factors enable the EU to behave differently than other actors in the international climate change process.

Bu tez uluslararası iklim değişikliği politikası ile küresel iklim müzakerelerindeki ana aktörlerin arasındaki ilişkiye odaklanmaktadır. Bu tezin temel amacı Avrupa Birliği'nin (AB) uluslararası iklim değişikliği müzakerelerinde diğer uluslararası aktörlerden farklı bir pozisyon almasını göstermektir. Bu farklılaşma Avrupa Birliği'nin kuruluş felsefesi ve AB'nin çevreci geleneğinden kaynaklanmaktadır. Bu tezin temel argümanı, genel anlamda ulus-devletler, özelde de büyük gaz emisyon yayıcısı devletler iklim değişikliği konusunda ulusal çıkarları çerçevesinde davranırken, Avrupa Birliği farklı bir şekilde davranmaktadır. Bu farklı davranış "davranış mantığı", "ulusüstü karar verme mekanizması" ve "AB'nin standartlarını yayma isteği" şeklinde üç unsurdan kaynaklanmaktadır. Aslında, Avrupa Birliği üyeleri arasında iklim değişikliği politikasında farklı görüşler olmasına rağmen, bu unsurlar uluslararası iklim değişikliğinde AB'nin diğer aktörlerden birlik seviyesinde farklı davranmasına imkan sağlamaktadır.
Küresel iklim değişikliği politikasında farklılaşan bir aktör olarak Avrupa Birliği
Keywords: Küreselleşme; İklim değişikliği; Great Emitters; Climate Change Negotiations; European Union; Birleşmiş Milletler İklim Değişikliği Çerçeve Sözleşmesi